Selection of maximal velocity of individual anaerobic threshold and its reproducibility by perception - Zhang, L.; Zhang, Y. L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The concept of "anaerobic threshold" is a very popular research topic in sports medicine and exercise physiology. It is still debatable with regard to how to choose maximal velocity of individual anaerobic threshold (VIATmax). The purpose of this study was to investigate VIATmax by using two folded breaking points of blood lactate threshold (TBLa) and ventilatory threshold (Tvent). The study will also investigate if VIAT max can be reproduced by perception (PVIATmax). Methods Twenty male participants participated in the study. They were divided into two groups based on their sports experiences: sports activists (Group 1) and semiprofessional long distance runners (Group 2). Three tests were complemented. First, participants performed an incremental exercise test (IET) on a treadmill at a speed of 3.0 m/sec for five minutes, with 0.4m/sec increments until participant accomplished 6 grades for 30 minutes. After two days the participants started a constant exercise test (CET) at VIATmax justified by individual TBLa and Tvent during IET. Test 3 was conducted after one-week rest. Before commencement of performance the instruction was given to each participant that he had to run as fast and cover as much distance as possible for 30 minutes. Running speed of treadmill was determined by the individual participant. Respired gas was continuously sampled by IMA for the analysis of gas exchange and ventilatory threshold. Blood sample was taken at the end of each 5 minutes stage to determine lactate threshold for each test. Results During IET the curve of blood lactate concentration shifted to the right with correspondence to different levels of endurance capability. There was no difference in VO2max between the two groups. However, maximal speed at VO2max in group 2 was significantly faster and value of VO2max (ml/Kg/min) was greater than that of group 1 (P<0.01). During CET BLa in all participants kept increasing during the first 15 minutes, and was changed greater than 1.0 mM./L. It was stabled after 15 min with the variation less than or at 0.5 mM/L to form an apparent plateau. The result of Test 3 indicated that maximal aerobic speed that each participant chose was considerably close to the VIATmax. The average difference of PVIAT and VIATmax was only 0.1 m/sec in group 1 and 0.08 m/sec in Group 2, respectively (P>0.05). Alteration of BLa and other physiological variables in Test 3 also displayed similar characteristics as compared to the values of Test 2. Discussion / Conclusions Intensity of anaerobic threshold is widely utilized for athletic training. But it is inaccurate since the breaking point of TBLa represents an increase of BLa at a point of five minutes. If a corresponding speed is roughly selected as VIATmax the possibility that VIATmax occurs between five minutes may be neglected. For further justification of VIATamx, Tvent was used and folded to the curve of TBLa to calibrate the speed of anaerobic threshold. Early work from Henritze defined MLSS as Bla change less than or at 0.5mmol/L during exercise. The result of Bla change at 0.5mmol/L in CET demonstrates that VIATmax justified by two folded breaking points of TBLa and Tvent in our study, is reliable and available. The finding that the MLSS were reproduced by PVIATmax demonstrates that the training of maximal aerobic power would become a positive process as long as the athlete or a normal person is instructed and practices at a possible accurate VIATmax, PVIATmax. A combination of two folded breaking points from TBLa and Tvent during IET is a reliable method to justify VIATmax. VIATmax can be perceived and controlled by athletes or non-athletes.